Synthesis of 5-Fluorouracil Derivatives as Possible Mutual Prodrugs with Meloxicam and Ibuprofen for Targeting Cancer Tissues - A.H. Dakhel, Zainab (Iraqi Journal of Pharmaceutical Sciences, 2017)
In the present study, five derivatives have been designed to be synthesized as possible mutual prodrugs for 5-Fluorouracil (5-FU) and non steroidal anti-inflammatory drugs (NSAIDs) to selectively deliver the drugs into the cancer cells. The synthesis of the target compounds were accomplished following multistep reaction procedures, the chemical reaction followed up and the purity of the products were checked by TLC. The structure of the final compounds and their intermediates were confirmed by their melting points, infrared spectroscopy and elemental microanalysis, the hydrolysis of compound III was studied using HPLC technique. According to the results mentioned above, compounds (Iâˆ’V) can be good candidates as possible mutual prodrugs of 5-FU and NSAIDs that can selectively deliver the parent drugs into the cancer cells by the effect of enzymes that elevated in tumor tissues compared with normal tissues. Key wards: Anticancer, 5-Fluorouracil, NSAIDs, prodrug.